Konsep Wilayatul Faqih Dan Supremasi Iran di Kawasan Timur Tengah - Bangkit Adi Saputra (Lembaga Pengkajian Pengembangan Pendidikan dan Kewirausahaan, 2025)
This research examines the concept of Wilayatul Faqih and its role in Iran's supremacy in the Middle East region. Using qualitative research methods through library research, this study analyzes how the Wilayatul Faqih concept has become the ideological foundation for Iran's foreign policy and regional hegemony strategy. The research employs hegemony theory to comprehensively analyze Iran's dominance mechanisms in the Middle East. The findings indicate that Wilayatul Faqih serves not only as a domestic governance system but also as a tool for projecting Iranian influence across the region through proxy groups, religious networks, and strategic alliances. The study concludes that Iran's regional supremacy is built upon the combination of religious legitimacy from Wilayatul Faqih and pragmatic geopolitical strategies.